Peculiarities of the fastness forming of the bars of the system Cold-box-amin - D. A. Kudin (Литьë и металлургия)
It is determined, that there exists direct relationship between the mechanism of the cover fastness forming and the mechanism of the mold core fastness forming. The methods of investigations of the physico-mechanical characteristics of polyurethane fdms can be used for study of characteristics of the binding materials of the Coldbox-amin system.